From Energy Efficiency to Carbon Neutrality: A Global Bibliometric Review of Energy Conservation and Emission Reduction in Building Stock - Junhong Liu; Shufan Zhang; Minda Ma; Ying He; Bo Wang (Buildings)
As a major contributor to global energy consumption and carbon emissions, the building sector plays a pivotal role in achieving carbon peaking and neutrality targets. This study systematically reviews the evolution of research on building stock energy conservation and emission reduction (BSECER) from 1992 to 2025, which is based on a comprehensive bibliometric analysis of 2643 publications. The analysis highlights the research contributions of countries, institutions, and scholars in the BSECER field, reveals patterns in collaborative networks, and identifies the development and shifting focus of research topics over time. The findings indicate that current BSECER research centers around four main areas: behavioral efficiency optimization, full life cycle carbon management, urban system transformation, and the integration of intelligent technologies, which collectively form a multiscale emission reduction framework from individual behavior to large-scale systems. Building on these insights, this study outlines five key future research directions: advancing comprehensive carbon neutrality technologies, accelerating the engineering application of intelligent technologies, developing innovative multi-scenario policy simulation tools, overcoming integration challenges in renewable energy systems, and establishing an interdisciplinary platform that links health, behavior, and energy conservation.